HUKUM JAMINAN DALAM PEMBIAYAAN DI PERBANKAN SYARI’AH - Lathif, Ah. Azharuddin (Fakultas Syariah, 2009)
Islamic banks have been developing rapidly during this decade. To some extent, it may show the Islamic monetary revival. One of the products introduced by Islamic banks in Indonesia is mudharabah. The original principle in mudharabah is without giving assurance. Nevertheless, in this transaction, no guarantees are provided to keep money well circulated in economic activities. Therefore, banks usually apply prudential principles before giving the credits to customers, such as demanding customers’ guarantees that they will return the money on time. Hence, this article aims at describing the urgency of assurance in mudharabah transaction.Bank Islam telah berkembang cepat selama sepuluh tahun terakhir ini. Hingga batas tertentu, hal itu menunjukkan kebangkitan keuangan Islam. Salah satu produk yang diperkenalkan oleh bank Islam di Indonesia adalah mudharabah. Prinsip mendasar dari mudharabah adalah ketiadaan kepastian. Meskipun demikian, daalam transaksi semacam itu, ketiadaan jaminan dimaksudkan untuk menjaga perputaran uang dalam aktifitas ekonomi. Oleh karena itu, bank biasanya menerapkan prinsip kehati-hatian sebelum memberikan kredit kepada nasabahnya, misalnya dengan meminta garansi dari nasabah bahwa mereka akan mengembalikan pinjaman tepat waktu. Artikel ini berusaha menggambarkan pentingnya jaminan dalam transaksi mudharabah.Keywords: Bank Islam, mudharabah, jaminan.